Dancing in Chains : the Youth of William Dean Howells. - Olsen, Rodney D. (UPCC book collections on Project MUSE., 1991)
"Dancing in Chains is far more than a sensitive biography (though it is surely that); it is also a model of psychologically informed social and cultural history. Olsen recognizes that psychic conflicts often play themselves out on a higher plane, that psychic and intellectual history are intertwined. He presents a wonderful nuanced picture of Howells."--Jackson Lears, Rutgers University. In this insightful study of the childhood and youth of William Dean Howells, Dancing in Chains demonstrates how the turbulent social and cultural changes of the early nineteenth century shaped the y.